Mobility Makes States : Migration and Power in Africa - Vigneswaran, Darshan; Quirk, Joel (Book collections on Project MUSE., 2015)
Human mobility has long played a foundational role in producing state territories, resources, and hierarchies. When people move within and across national boundaries, they create both challenges and opportunities. In Mobility Makes States, chapters written by historians, political scientists, sociologists, and anthropologists explore different patterns of mobility in sub-Saharan Africa and how African states have sought to harness these movements toward their own ends.While border control and intercontinental migration policies remain important topics of study, Mobility Makes States demonstrates that immigration control is best understood alongside parallel efforts by states in Africa to promote both long-distance and everyday movements. The contributors challenge the image of a fixed and static state that is concerned only with stopping foreign migrants at its border, and show that the politics of mobility takes place across a wide range of locations, including colonial hinterlands, workplaces, camps, foreign countries, and city streets. They examine short-term and circular migrations, everyday commuting and urban expansion, forced migrations, emigrations, diasporic communities, and the mobility of gatekeepers and officers of the state who push and pull migrant populations in different directions. Through the experiences and trajectories of migration in sub-Saharan Africa, this empirically rich volume sheds new light on larger global patterns and state making processes.Contributors: Eric Allina, Oliver Bakewell, Pamila Gupta, Nauja Kleist, Loren B. Landau, Joel Quirk, Benedetta Rossi, Filipa Ribeiro da Silva, Simon Turner, Darshan Vigneswaran.